Trihalomethanes and physicochemical quality of drinking water in Addis Ababa, Ethiopia - Nebiyou Tafesse; Massimiliano Porcelli; Belachew Bacha Hirpessa; Janvier Gasana; R.K. Padhi; Sirak Robele; Argaw Ambelu (Heliyon, 2023)
Background: Trihalomethanes (THMs) are the most dominant fraction of all the byproducts formed during chlorination of water. Disinfection by product (DBP) formation in water is a function of numerous factors, including pH, temperature, residual chlorine, source water characteristics, and organic matter. No study has determined the THM level in the drinking water supply of Addis Ababa, Ethiopia. Methods: A cross-sectional design was conducted to collect water samples in the water supply distribution networks of Addis Ababa, Ethiopia. Twenty-one (21) sampling stations yielded a total of one hundred twenty (120) samples of drinking water. The sample handling and collection procedures were carried out in accordance with USEPA guidelines. A DB-5 capillary column was used to separate the THMs, which were detected using GC-ECD (gas chromatography-electron capture detector). Spectrophotometric and in situ methods were used for physicochemical parameters. Redundancy analysis (RDA) was used for data analysis of trihalomethanes and environmental variables using CANOCO 4.5. Results: The mean concentration of total trihalomethanes in drinking water in Addis Ababa was 76.3 μg/L. The concentration of chloroform in the drinking water supply in Addis Ababa, Ethiopia, ranged between 4.03 and 79.4 μg/L. The mean total THMs in the Legedadi and Gefersa water supply systems were 77.4 μg/L and 69.66 μg/L, respectively. The residual chlorine, phosphates, UV absorbance at 254 nm, and combined chlorine had positive correlations with THM formation. However, electron conductivity had a negative correlation with THM formation. Conclusions: Chloroform contributed the most to TTHMs in nearly all samples. The residual chlorine, UV absorbance, phosphate and hardness as calcium, and electron conductivity were found to be the main predictors determining the abundance and distribution of trihalomethanes. The monitoring and regulation of the THMs is required on a regular basis to analyse trends and guide the water treatment and distribution system.